2016
DOI: 10.1016/j.foodchem.2016.04.123
|View full text |Cite
|
Sign up to set email alerts
|

Potato wound-healing tissues: A rich source of natural antioxidant molecules with potential for food preservation

Abstract: The need for safe, effective preservatives is a prominent issue in the food and drug industries, reflecting demand for natural alternatives to synthetic chemicals viewed as harmful to consumers and the environment. Thus, this study determined the identities and scavenging capacities of antioxidant metabolites produced as a response to potato tuber wounding, using activity-guided fractionation of polar extracts from a Yukon Gold cultivar that had previously exhibited exceptionally high radical-scavenging activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…Antioxidants have wound healing properties and can protect tissues from oxidative damage31. CMLA possesses antioxidant activity as it increased the activities of antioxidant enzymes in tissue homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants have wound healing properties and can protect tissues from oxidative damage31. CMLA possesses antioxidant activity as it increased the activities of antioxidant enzymes in tissue homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…2 Different types of antioxidants have been used for wound healing to eliminate the destructive effects of free radicals. [3][4][5] Taurine (2-aminoethane sulfonic acid), a non-essential sulfur-containing amino acid found in large amounts in most mammalian tissues, is a powerful antioxidant which has positive effects on inflammation, cell proliferation, and collagen synthesis. 6 These include the cell membrane stabilization, modulation of the calcium level, osmoregulation, and antiapoptotic, antioxidant, and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…The PCA analysis of the thermo-desorption GC data indicates that specific volatiles are produced in non-infected tubers during healing. Dastmalchi et al (2016) identified nine constituents with high antioxidant properties during the wound healing process. These molecules have a high molecular weight and were extracted/measured with liquid chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have a high molecular weight and were extracted/measured with liquid chromatography. These molecules were not measured in our experiment as the sampling and the analysis methods differed from the ones used by Dastmalchi et al (2016).…”
Section: Discussionmentioning
confidence: 99%